Pengaruh Perbedaan Jenis Garam terhadap Kandungan Metabolit pada Fermentasi Kimchi: Reviu - Fannisa Hafidhia Suryana (Integrasi: Jurnal Studi Islam dan Humaniora, 2023)
Kimchi is a food produced through a traditional fermentation process in vegetables to keep the texture of vegetables crispy and fresh. Compounds produced in kimchi fermentation are mannitol and some sugars such as glucose, sucrose, and maltose. The fermentation used in its manufacture uses Lacto fermentation which involves Lacto Acid Bacteria (LAB). In addition, the addition of salt is done for preservation and to determine the level of mannitol levels. The types of salt used are pure salt and mineral salt. Pure salt contains pure NaCl while mineral salt contains NaCl and other mineral metals such as Ca, Mg, and Mn. The purpose of reviewing this article is to determine the effect of different types of salt on the type of metabolite content in kimchi fermentation. The research method used is the collection of sources and data related to the topics discussed. The applied literature study uses a deductive approach based on sources from journal literature by utilizing search engines on Google Scholar, ACS, ScienceDirect, KoreaScience, PubMed, SpringerLink and supporting literature websites (joybileefarm.co, baechukimchi.ca). The results obtained show that there is an effect of different types of salt on the metabolite content in kimchi which is shown in the data pattern. Conclusion: that the effect of adding pure and mineral salts indicates an increasing ratio of Latilactobacillus bacteria resulting in metabolites with different patterns.